Flipbook Learning Source (FLS) Based on Socio Science Issues (SSI): Effectiveness for increasing Junior High School Students' Science Literacy - Indrawati,; Astutik, Sri; Handayani, Rif’ati Dina; Narulita, Erlia; Putra, Pramudya Dwi Aristya; Wicaksono, Iwan (Advances in Social Sciences Research Journal, 2023)
In the development of information technology, knowledge about natural sciences is increasingly easy to obtain. Scientific literacy skills are part of the 21st century skills that students must have so that they can adapt to complex problems that may occur in their surrounding environment. Electronic textbooks that can encourage students to practice using scientific literacy skills that can be used to identify and analyze scientific problems around students until they can be solved. Flipbook Learning Source (FLS) based on Socio Science Issues (SSI) is an electronic textbook that is interpreted as a social issue with a scientific context that connects students with scientific discussions developing in society to be explored. The aim of this research is to examine the effectiveness of SSI-based FLS for increasing junior high school students' scientific literacy. Development research stages based on 4-D development research design. This research was carried out at junior high schools in the Besuki Ex-Karisidenan. Time for conducting research in Odd Semester 2022/2023. The results of the N-Gain Score test were carried out to determine the increase in students' scientific literacy, the average increase was 0.48 in the medium category. Scientific literacy abilities can be demonstrated from students' ability to use scientific knowledge, identify questions and be able to draw conclusions based on facts that occur in the natural environment and be able to make decisions in the process of change. Scientific literacy skills enable students to analyze scientific problems that exist in everyday life.